Transcendence in Pathological Forms of the Language - HOVHANNISYAN, SIRANUSH (Bulletin of Yerevan University B: Philology, 2021)
The article deals with the transcendence of unhealthy language forms. From observations, it is concluded that healthy and pathological types of speech, united in a common system of language, are transcended in different ways. In the case of pathological forms of language, unlike healthy ones, the content and form are transcended separately from each other. In the formal plan, they ultimately amount to an absolute unit, and in terms of content – to an absolute set.
Keywords: language megasystem, language nanosystem, absolute prototype, absolute essence, cognition, objective reality, transcendent sphere